Efficacy of chronic neck pain self-treatment using press needles: a randomized controlled clinical trial - Horike, Kaori; Ukezono, Masatoshi (Frontiers in Pain Research, 2024)
Background Chronic neck pain is common among Japanese individuals, but few receive treatment. This randomized controlled trial aimed to evaluate the efficacy of acupuncture using press needles in the self-treatment of chronic neck pain and preliminarily identify the characteristics of patients likely to benefit from this treatment. Methods Fifty participants with chronic neck pain were allocated to receive either press needle or placebo treatment for 3 weeks. The visual analogue scale (VAS) and motion-related VAS (M-VAS) scores for neck pain, Neck Disability Index score, and pressure pain threshold were measured at baseline, after the first session, at the end of the last session, and 1 week after the last session. Changes in the outcomes were analyzed using analysis of variance, and the relationships between the variables were evaluated using structural equation modeling. Results Intervention results as assessed by VAS score revealed no significant differences in the ANOVA. A between-groups comparison of M-VAS scores at the end of the last session and baseline showed a significant difference (press needle: −21.64 ± 4.47, placebo: −8.09 ± 3.81, p = 0.025, d = −0.65). Structural equation modeling revealed a significant pain-reducing effect of press needle treatment (β = −0.228, p = 0.049). Severity directly affected efficacy (β = −0.881, p < 0.001). Pain duration, baseline VAS and Neck Disability Index scores were variables explaining severity, while age and occupational computer use were factors affecting severity. Conclusion Self-treatment with press needles for chronic neck pain did not significantly reduce the VAS score compared to placebo but reduced the motion-related pain as assessed by M-VAS score. A direct association was observed between pain severity and the effectiveness of press needles, and the impact of age and computer were indirectly linked by pain severity. Clinical Trial Registration Identifier UMIN-CTR, UMIN000044078.